Gambaran Keikhlasan pada Relawan Zakat (Perspektif Psikologi Islam) - Riska Rahma Suciyani; Gadis Deslinda (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2026)
Sincerity is a simple trait to talk about, but ultimately very difficult to practice. In addition, the trait of riya' (showing off) is feared to be one of the factors that can undermine a person's intention to be sincere in helping others. Preliminary studies show that there are still other motives and behaviors similar to riya' and other purposes among zakat volunteers. Objective: The purpose of this study is to determine the description of sincerity among zakat volunteers, specifically volunteers from the Solo branch of Lazismu Central Java. Method: The informants in this study were zakat volunteers with the following criteria: male/female students aged 18-24 years old, and directly involved in the Solo branch of Lazismu Central Java. There were 4 informants. The data source used was primary data. Sampling was conducted using purposive sampling. The data collection technique used in this study was semi-structured interviews.  The data analysis technique used the Atlas.ti application and the Interactive Analysis Model technique from Miles and Huberman. Results: The results of the study show that there are main themes that can describe the sincerity of volunteers in carrying out their duties as zakat volunteers, namely: : (1) motivation to become a volunteer, (2) response to conflict, (3) social appreciation, and (4) intention. The informants in this study tend to behave sincerely in their roles as zakat volunteers within the zakat institution.